Survey of audiovisual standards and practices in health sciences libraries. - McCarthy, J (1983)
A survey of audiovisual (AV) practices in health sciences libraries was conducted by the Audiovisual Standards and Practices Committee of the Medical Library Association. The objective was to determine the variety and extent of AV practices currently in use in health sciences libraries, as a preliminary step toward developing AV standards.